Uric acid reduces the expression of aquaporins in renal collecting ducts to increase urine output in hyperuricemia - Cui, Xiaohui; Qiao, Rongfang; Wang, Bing; Hu, Yitong; Sun, Guoying; Hu, Wenjuan; Luan, Zhilin; Ren, Huiwen; Xu, Hu; Guan, Youfei; Zhang, Xiaoyan (Frontiers in Physiology, 2025)
BackgroundHyperuricemia (HUA) has attracted wide attention due to its close relationship with gout, hypertension, hypertriglyceridemia, obesity, atherosclerotic heart disease, type 2 diabetes and chronic kidney disease. Clinical observations suggest that people with high levels of serum uric acid (sUA) exhibits impaired urine concentration. We speculate that UA may regulate the expression of AQPs through inflammatory pathways, resulting in impaired renal urine concentration.Methods and resultsWe revealed that patients and mice with HUA had a polyuria phenotype and found that the expression of aquaporin 2 (AQP2), AQP3 and AQP4 were significantly reduced in the kidneys of mice with HUA. Similarly, uric acid (UA) treatment markedly suppressed the expression of AQP2, AQP3 and AQP4 in cultured inner medullary collecting duct cells (IMCDs). We observed an increased expression of NF-κB in the kidneys of mice with HUA and in the IMCD cells treated with UA. Blockade of NF-κB by its inhibitor Bay 11-7082 dramatically attenuated UA-suppressed expression of AQP2, AQP3 and AQP4. Furthermore, the luciferase reporter, CHIP and EMSA assays showed that NF-κB can directly bind to the promoter regions of AQP2, AQP3 and AQP4 genes to suppress their transcription.ConclusionOur findings demonstrate that UA reduces the expression of AQP2, AQP3 and AQP4 in an NFκB-dependent manner, which contributes to the polyuria phenotype in the subjects with HUA.